Barbie and the magic of Pegasus - Lions Gate Home Entertainment ([United States] : Lions Gate Entertainment Home Entertainment, 2005)
Princess Annika escapes the clutches of an evil wizard, explores the wonders of Cloud Kingdom, and teams up with a magnificent winged horse to defeat the wizard and break the spells that imprison her family.
MPAA rating: Not rated.
DVD, region 1, widescreen presentation; 5.1 and 2.0 Dolby Digital.
English or Spanish dialogue; closed-captioned.
Keywords: Barbie (Fictitious character) -- Juvenile drama; Pegasus (Greek mythology) -- Juvenile drama; Princesses -- Juvenile drama; Feature films; Animated films; Children's films; Video recordings for the hearing impaired